Biopsychosocial Models of Peripartum Depression: A Narrative Review - Maja Žutić (Clínica y Salud. Investigación Empírica en Psicología, 2023)

(untitled)
Background: Peripartum depression (PPD) is a prevalent, heterogeneous disorder with various underlying mechanisms and unwanted outcomes. Substantial uncertainty surrounding PPD aetiology exists. To comprehensively investigate PPD, research is adopting the biopsychosocial theoretical model highlighting the interplay between biological and psychosocial factors. This paper aims to provide an overview of risk factors and biopsychosocial models of PPD. Method: A literature search was conducted in databases to identify risk factors and biopsychosocial models of PPD. Results: The most robust biological and psychosocial risk factors of PPD and findings from integrative studies are outlined. Several biopsychosocial models are identified, explaining antepartum, postpartum or peripartum depression. Integrative models show promise but differ in conceptualisation and proposed aetiological pathways underlying PPD. Conclusion: Biopsychosocial principles should be applied throughout the perinatal research and healthcare provision as a necessary landmark towards guiding future theory, improving maternal mental health care and ensuring better outcomes for mothers and children.